Broad geographical distribution of a cytotoxin gene mediating beta-hemolysis and bacteriocin activity among Streptococcus faecalis strains. - LeBlanc, D J (1983)
Conjugative hemolysin-bacteriocin plasmids were isolated from Streptococcus faecalis var. zymogenes strains of diverse geographical origins. Cloned DNA fragments containing the hemolysin-bacteriocin gene(s) from one of these plasmids (pAD1) hybridized to two EcoRI fragments of identical size from each of the five plasmids examined. Results of hybridization experiments in which total plasmid DNA was used suggested that the plasmids shared extensive homology. Two of the plasmids, pAD1 from strain DS16 (Ann Arbor, Mich.) and pAM gamma 1 from strain DS5 (Miami, Fla.), were 100% homologous and had identical EcoRI restriction patterns (eight fragments each). There was no detectable homology between the plasmid-mediated hemolysin determinants of S. faecalis and DNA from other beta-hemolytic streptococci (Lancefield groups A, B, F, or H).